The big New Yorker book of dogs - 20160731 frey50 (New York : Random House, 2012)
A collection of anecdotes, essays, fiction pieces, and illustrations-- all about dogs, and all from the pages of New Yorker magazine. From Charles Addams to E.B. White, this book is a gift to dog lovers everywhere.
Foreword / Malcolm Gladwell -- Good dogs -- Bad dogs -- Top dogs -- Under dogs -- A note on Thurber's dogs / Adam Gopnik.
Keywords: Dogs